1985
DOI: 10.1139/f85-061
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination d'un stock de poisson, l'anguille (Anguilla rostrata), basée sur la présence d'un produit chimique de synthèse, le mirex

Abstract: Mirex concentrations were measured in eels (Anguilla rostrata) from eastern Canada to determine the contribution of Lake Ontario eels to the Saint Lawrence commercial fishery. Mirex could be detected in all eels (50 specimens) collected in Lake Ontario (0.18 ± 0.11 μg∙g−1). Most sedentary eels collected from the Saint Lawrence commercial fishery and both the migratory and sedentary eels collected from the Saint Lawrence tributaries and the Maritimes had no mirex. Of the migrating eels collected in the Saint La… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0
1

Year Published

1987
1987
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 0 publications
1
9
0
1
Order By: Relevance
“…Salinity at Quebec City ranges from 0-1 ppm while the surface salinity at Kamouraska fluctuates from 18 to 24 ppm (Dutil et al, 1987). The eel fisheries in both Quebec City and Kamouraska consist entirely of out-migrating adults (Dutil et al, 1985) while Lake St Lawrence contains resident yellow eels throughout the year and also functions as a migratory corridor for maturing silver phase eels from Lake Ontario and its associated watersheds, and the upper St Lawrence River.…”
Section: Study Areamentioning
confidence: 99%
“…Salinity at Quebec City ranges from 0-1 ppm while the surface salinity at Kamouraska fluctuates from 18 to 24 ppm (Dutil et al, 1987). The eel fisheries in both Quebec City and Kamouraska consist entirely of out-migrating adults (Dutil et al, 1985) while Lake St Lawrence contains resident yellow eels throughout the year and also functions as a migratory corridor for maturing silver phase eels from Lake Ontario and its associated watersheds, and the upper St Lawrence River.…”
Section: Study Areamentioning
confidence: 99%
“…Bes anguilles argent6es du Saint-Laurent ktaient beaucoup plus contaminees et avaient une plus forte prevalence de difformites et de lesions qu'un stock de reference bien qu'elles 6taient en moyenne moins contaminkes en 1990 qu'en 1982 (BPC : 1,12 versus 4,54 p,gsg-'; mirex : 0,025 versus 0.07 p,g-g-'). Des cas de toxicit6 Ii.tale due a la contamination chimique sont rapport& (Dutil et al 1985), the only Great Lake where eels are commonly found (Scott and Crossman 1973). Concern for this recruitment decline to the St. Lawrence River prompted an investigation s f its possible causes.…”
unclassified
“…This study formed part of a program on the impact of contaminants on the health of eels (Hodssn et al 1992(Hodssn et al , 1994 and the role of eels as vectors of contaminants to beluga whales (Delphinapterus Eeusces) (Hickie et al 1991). Tn this study, "stock" refers to a production or a management unit, as defined by Larkin (1972), and as used previously for this species (Dutil et al 1985;Castonguay et al 1989 Eckersley (19821, Hendrick (1991), and M.J. Eckersley (unpublished data). Eels were not counted in 1980.…”
mentioning
confidence: 99%
“…In 2006, the Committee on the Status of Endangered Wildlife in Canada (COSEWIC) issued a status report for A. rostrata and gave the designation of special concern based on the data series available (COSEWIC, 2006). Among the causes responsible for the decline, habitat alteration and dams were highlighted as significant threats especially in the upper St Lawrence River and Lake Ontario (USLRLO) where the collapse of this component may significantly affect total reproductive output for the species (Castonguay et al , 1994 b ) because of the female‐dominated sex ratio (Dutil et al , 1985; Couillard et al , 1997) and the highest individual fecundity in the whole distribution range, with a mean of 14·5 million oocytes (Tremblay, 2009). Construction of dams on rivers and lake outlets are known to be detrimental to this species, by preventing or impeding free access to growth habitat upstream (Legault, 1988; Lary & Busch, 1997; Verdon et al , 2003) and by increasing mortality through turbine passage during downstream migration at dams equipped with hydroelectric facilities (Mitchell & Boubée, 1992; McCleave, 2001; Verreault & Dumont, 2003).…”
Section: Introductionmentioning
confidence: 99%